Are coagulase-negative staphylococci virulent?. (September 2019) - Heilmann, C.; Ziebuhr, W.; Becker, K.
Abstract: Background: Progress in contemporary medicine is associated with an increasing number of immunocompromised individuals. In this vulnerable group, the underlying disease together with long-term hospitalization and the use of medical devices facilitate infections by opportunistic pathogens, of which coagulase-negative staphylococci (CoNS) represent a prime example. Objectives: The diversity of CoNS with species- and strain-specific differences concerning virulence and clinical impact is highlighted. A focus is on the ability of CoNS to generate biofilms on biotic and abiotic surfaces, which enables skin and mucosa colonization as well as establishment of CoNS on indwelling foreign bodies. Sources: Literature about the virulence of CoNS listed in PubMed was reviewed. Content: Most catheter-related and prosthetic joint infections as well as most other device-related infections are caused by CoNS, specifically by Staphylococcus epidermidis and Staphylococcus haemolyticus. A common theme of CoNS infections is a high antibiotic resistance rate, which often limits treatment options and contributes to the significant health and economic burden imposed by CoNS. Implications: Breaching the skin barrier along with the insertion of medical devices offers CoNS opportunities to gain access to host tissues and to sustain there by forming biofilms on foreign body surfaces. Biofilms represent the perfect niche to protect CoNS from both the host immune response and the action of antibiotics. Their particular lifestyle, combined with conditions that facilitate host colonization and infection, has led to the growing impact of CoNS as pathogens. Moreover, CoNS may serve as hidden reservoirs for antibiotic resistance and virulence traits.